Política das ruas e das redes : autoexposição e anonimato nas multidões de Junho de 2013 - Márcia Maria da Cruz (2018)
The political protests that occur in June 2013 in São Paulo and Belo Horizonte are the focus of this thesis. The question arises: what constitutes the common in times of personalization of political actions, especially in a context of strong interconnections between Web networks and streets? It is argued that the common of contemporary collective actions depends on peculiarities and incorporate two seemingly antithetical phenomena, that are in fact correlated: self-exposition and anonymity. The protesters sometimes stand out in the crowd, sometimes merge amid the collective, standing out and merging simultaneously. In order to address these phenomena, this thesis integrates the concepts of multitude (Hardt and Negri, 2015), disidentification (Rancière, 1996) and performativity (Butler 2014 [1990], 2016). Empirical work was structured in two fronts. The first one consisted of a set of 50 semi-structured interviews with activists from Belo Horizonte and São Paulo, using the snow ball technique. The second front looked at a sample of 306 posts published on Facebook by Movimento Passe Livre (MPL) and by Anonymous Brasil, along with thread comments related to these posts. The analysis was performed from the identification of markers of selfexposure and anonymity, aiming to explore how such phenomena are articulated in the configuration of neoteric protests and in the weaving of the common that rely on singularity. We identify as self-exposition markers: a profusion of personal reports, display of selfies, corporeal and expressive occupation of public spaces (including posters, colors and performances) and the viralization of personal contents in the form of memes and correlates. The anonymity is clearly denoted by the use of masks and scarves; in multitudinous images; in the occupation of public spaces in which bodies are diluted (colors, sea of posters, choral speaking) and in the ciphered nature of some memes. Through anonymity and self-exposure, the subjects shift from pre-established identities, in a disidentification process that allows the emergence of new processes of subjectivation and the construction of common. The results of the analysis indicate that affection plays a fundamental role in articulating the protesters, although being on the streets is not restricted to their passionate dimension. The shared images suggest that the crowd presents itself as a political body, granting new features to the sea of differences that constitute that body. We conclude that the acts of June 2013 allowed the subjects to experimentat new ways of organizing themselves collectively. The character and role of leadership were examined, leading to questioning of the idea of representation in effect. The personalization of politics involves new forms of drafting that reflect in the field of culture and the way people perform publicly, in the expression of their own existence over the cities. The narratives that flow from the experience of the subjects, rather than the process of self-understanding, foster forms of action that organize the sensible by creating new landscapes for the constitution of the common.